THU0341 Expansion of CD4+CXCR3+ T Cells in Patients with Systemic Lupus Erythematosus (SLE) Correlates with Subclinical Atherosclerosis. (23rd January 2014) - Sacre, K.; Escoubet, B.; Charles, N.; Chauveheid, M.-P.; Papo, T.
Abstract : Background: The mechanisms for accelerated atherosclerosis in SLE remain unclear (1 ). As atherosclerosis is itself immune-mediated, features of SLE-associated immunity might explain accelerated cardiovascular disease beyond traditional cardiovascular risk factors. Objectives: We hypothesized that T cells expressing CXCR3, a chemokine receptor involved in T cells transendothelial migration, play a role in the induction of SLE-associated atherosclerosis. Methods: The expression of CXCR3 was measured on PBMCs by flow cytometry in 33 SLE subjects asymptomatic for cardiovascular diseases and 18 controls. Patients with SLE were assessed for subclinical vascular disease with common carotid artery intima-media thickness (IMT), internal carotid artery wall thickness (ICWT), pulse wave velocity (PWV), and pulse pressure (PP) measurements. SLE disease history, corticoid exposure and classical risk factors for cardiovascular disease were systematically recorded. Results: All SLE subjects had received long-term glucocorticoid and 24 (73%) were still under prednisone at a mean daily dose of 8.7 + 2.6 mg/day. All were receiving hydroxychloroquine. Twenty-four had been treated with immunosuppressive or immunomodulatory drugs during follow-up. Four patients also had antiphospholipid syndrome. Classical cardiovascular risks distribution did not differ between controls and SLE patients (Table 1 ) SLE-subjects displayed a higher frequency of circulating CD4 + T cells (35.1±17.7 vs 23.6±8.4%; p<0.05), CD8 + T cells (72.4±19.5 vs 44.9±14.9%; p<0.005), NKT cells (56.9±19.1 vs 31.3±18.8%; p<0.001) and B cells (24.5±16.1 vs 12.4±5.9%; p<0.05) that expressed the chemokine receptor CXCR3, as compared to controls. The percentage of NK cells, classical and pro-inflammatory monocytes expressing CXCR3 did not differ between groups. The mean IMT, ICWT, PWV and PP in SLE subjects were 0.54 (±0.12) mm, 1.34 (±0.74) mm, 7.1 (±1.65) m/s and 54.7 (± 13.3) mmHg, respectively. In SLE subjects, infraclinical vascular disease -assessed with IMT (r 2 =0.15, p=0.02), ICWT (r 2 =0.12, p=0.04), PWV (r 2 =0.12, p=0.04), and PP (r 2 =0.23, p=0.004)- correlated with expression of CD4 + CXCR3 + on T cells. Interestingly, CD4 + CXCR3 + T cells were shown to be antigen-primed CD45RA - CD27 +/- and to produce high levels of TNF-α upon polyclonal TCR activation. No significant association was found between peripheral expansion of CD4 + CXCR3 + T cells and traditional (Framingham score, LDL-cholesterol), non-traditional (HbA1c, homocystein, 25(OH)-D3 vitamin; creatinine blood levels) cardiovascular risk factors or SLE-related risk factors (duration of disease, glucocorticoid therapy, SLEDAI score, renal function). Conclusions: Our study suggests that CD4 + CXCR3 + T cells are instrumental in SLE-associated atherosclerosis. References: Skaggs BJ, et al. Nat Rev Rheumatol. 2012;8:214-23. Disclosure of Interest: None Declared